How Do Sellers Benefit From Buy-It-Now Prices in Ebay Auctions? – an Experimental Investigation - Tim Grebe; Radosveta Ivanova-Stenzel; Sabine Kröger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
In Buy-It-Now (BIN, hereafter) auctions, sellers can make a ẗake-it-or-leave-itp̈rice offer (BIN price) prior to an auction. We analyse experimentally how eBay sellers set BIN prices and whether they benefit from offering them. Using the real eBay environment in the laboratory, we find that the eBay auction format supports deviations from truthful bidding leading to auction prices substantially below those expected in second-price auctions. Our results reveal that the observed price deviations are not an artefact due to the existence of the BIN price, rather a consequence of the specific features of the eBay-auction format - a mixture between sealed-bid and open second-price auction with a fixed end-time. Moreover, we find that information available on eBay can be used as indicator for the price deviation and that sellers respond strategically to this information. Seller risk aversion does not affect BIN prices and more experienced sellers ask for higher BIN prices. The introduction of BIN prices to eBay auctions has an enhancing effect: the eBay BIN auction is more efficient and generates significantly higher revenue compared to a standard eBay auction without a BIN price.
Keywords: C72; C91; D44; D82; L01; 330; experience; online markets; ebay; bin price; private value; experiment